2021
DOI: 10.1371/journal.pntd.0008935
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNAseq analyses at soma and germline levels reveal evolutionary innovations in the elephantiasis-agent Brugia malayi, and adaptation of its Wolbachia endosymbionts

Abstract: Brugia malayi is a human filarial nematode responsible for elephantiasis, a debilitating condition that is part of a broader spectrum of diseases called filariasis, including lymphatic filariasis and river blindness. Almost all filarial nematode species infecting humans live in mutualism with Wolbachia endosymbionts, present in somatic hypodermal tissues but also in the female germline which ensures their vertical transmission to the nematode progeny. These α-proteobacteria potentially provision their host wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Contrasting depletion levels by lowered dose exposures of anti- Wolbachia drugs in different filarial tissues may reflect effect site pharmacokinetics (i.e., local drug penetration or drug detoxification) or that the Wolbachia residing in the reproductive tissues are intrinsically more sensitive to drug activity, potentially via virtue of higher division rate and metabolic activity. Recent dual RNAseq analysis of Wolbachia gene transcription in the hypodermal vs. the ovarian population within B. malayi indicates a relatively harsher environment in the former location, reflected by upregulation of bacterial stress response proteins, which may impinge on endobacterial growth (Chevignon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting depletion levels by lowered dose exposures of anti- Wolbachia drugs in different filarial tissues may reflect effect site pharmacokinetics (i.e., local drug penetration or drug detoxification) or that the Wolbachia residing in the reproductive tissues are intrinsically more sensitive to drug activity, potentially via virtue of higher division rate and metabolic activity. Recent dual RNAseq analysis of Wolbachia gene transcription in the hypodermal vs. the ovarian population within B. malayi indicates a relatively harsher environment in the former location, reflected by upregulation of bacterial stress response proteins, which may impinge on endobacterial growth (Chevignon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that transcription levels of the w Bm0076 gene are highest in the body wall and ovaries of the adult female B . malayi , suggesting the effector is involved in either w Bm exit from body wall tissues or invasion of ovaries in this maturation step [ 85 ]. B .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, much of the literature on filarial nematodes and Wolbachia focuses on the involvement of T4SS, which facilitate the transport of molecules from bacteria to the inside of host cells. In particular, T4SS is a major exchanger of effector proteins and small metabolites such as nucleotides and their precursors, and it is involved in the control of gene expression and germline development in filarial nematodes ( Rancès et al, 2008 ; Slatko et al, 2010 ; Darby et al, 2012 ; Li and Carlow, 2012 ; Carpinone et al, 2018 ; Lindsey, 2020 ; Chevignon et al, 2021 ). Our data identified an ATPase component of the T4SS and also two components of the T1SS, another key bacterial secretion system that translocates proteins across the outer membrane into the extracellular space.…”
Section: Discussionmentioning
confidence: 99%